Penerapan Aplikasi Sistem Keuangan Desa (SISKEUDES) untuk Penyusunan APB Desa di Desa Karangsono - Oktavie Fresiliasari (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to find out the application of the Village Financial System Application (SISKEUDES) is very important to improve the preparation of the Village APB financial statements. This implementation makes a significant contribution to the realization of transparent and accountable management of village fund allocation, resulting in good governance. The research was conducted in Karangsono Village, Mranggen District, Demak Regency. The method used is a qualitative method, especially using a case study approach with in-depth interviews and direct observation. Participants in this study were selected through purposive sampling techniques based on certain criteria, in this case the participants taken from the village apparatus were the Village Head, Head of Finance and Head of Planning. Furthermore, the conclusion of the research results shows that the readiness of the Karangsono Village Government in implementing the Siskeudes application is good. The benefits in the preparation of the Village APB through the Siskeudes application are very helpful in accelerating financial reporting. The Siskeudes application also helps in real time monitoring, automatic calculation and reporting very easily. So that with the Siskeudes application, the performance of the village apparatus is getting better and the results are very significant. It's just that from the implementation of Siskeudes, there are still obstacles from human resources that lack of training and age factors. But over time, Siskeudes operators can adjust the development of the Siskeudes application itself.